2016
DOI: 10.1149/2.0641702jes
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—Silicon Electrodeposition in a Water-Soluble KF–KCl Molten Salt: Utilization of SiCl4as Si Source

Abstract: The electrodeposition of Si was investigated in a molten KF–KCl salt mixture (eutectic composition, 45:55 mol%) after the introduction of SiCl4 to demonstrate a new production method for solar cell substrates. Gaseous SiCl4 was introduced directly into the molten salt at 1023 K by a vapor transport method using Ar as a carrier gas. The dissolution efficiency of SiCl4 exceeded 80% even when a simple tube was used for bubbling. Galvanostatic electrolysis was conducted at 923 K on a Ag substrate at 155 mA cm−2 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Moreover, owing to the low solubilities of LiF and NaF in water, it is difficult to remove the adhered salt from the electrodeposited silicon films. [23] Recently, a water soluble KCl-KF salt was employed to prepare a thick (more than 50 µm) silicon film or silicon coatings by electrodeposition, [24][25][26][27] yet no photoresponse has been demonstrated. Since the solubility of K 2 SiF 6 in KCl-KF at 650 °C is much higher than that of SiO 2 in CaCl 2 at 850 °C, in the present study the feasibility of preparing a thick (>10 µm) and dense silicon film with photoactivity on a sheet substrate in KCl-KF-K 2 SiF 6 bath was investigated and a successful formulation was discovered.…”
mentioning
confidence: 99%
“…Moreover, owing to the low solubilities of LiF and NaF in water, it is difficult to remove the adhered salt from the electrodeposited silicon films. [23] Recently, a water soluble KCl-KF salt was employed to prepare a thick (more than 50 µm) silicon film or silicon coatings by electrodeposition, [24][25][26][27] yet no photoresponse has been demonstrated. Since the solubility of K 2 SiF 6 in KCl-KF at 650 °C is much higher than that of SiO 2 in CaCl 2 at 850 °C, in the present study the feasibility of preparing a thick (>10 µm) and dense silicon film with photoactivity on a sheet substrate in KCl-KF-K 2 SiF 6 bath was investigated and a successful formulation was discovered.…”
mentioning
confidence: 99%
“…[93] Yasuda reported that silicon could electrodeposit from SiCl 4 in molten salt KF-KCl. [94] Other similar works focus on the adjustment of molten salt and the optimization of experimental parameters. [95][96][97] However, there are still some defects, such as high cost, the strong corrosiveness of fluoride at high temperature, which would lead to the appearance of impurities.…”
Section: Molten Salt-assisted Reductionmentioning
confidence: 99%
“…One of the cheapest and promising methods for producing nanosized silicon is electrolytic reduction from molten salts. To date, many studies have been carried out aimed at the electrolytic production of silicon from various molten electrolytes with K 2 SiF 6 , Na 2 SiF 6 , SiO 2 , and SiCl 4 additives in a temperature range mainly from 550 • C to 750 • C [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. All these studies show the fundamental possibility of using electroreduction for the production of silicon deposits of various morphologies, including continuous coatings up to 1 mm thick, submicron films (0.5-1 µm), micro-sized dendrites, nano-and micro-sized disordered fibers.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising electrolytes for silicon production is the KCl-KF melt with a KF molar fraction of up to 66% [27][28][29][30][31], which is a good solvent for K 2 SiF 6 and SiO 2 and is water soluble. However, this system also has a number of disadvantages, including relatively high aggressiveness of KF to reactor materials, the need to remove impurities such as H 2 O and HF from KF when preparing a molten KCl-KF mixture, and a good solubility of oxides.…”
Section: Introductionmentioning
confidence: 99%